2021
DOI: 10.1111/trf.16327
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 antibody screening with SARS‐CoV‐2 red cell kodecytes using routine serologic diagnostic platforms

Abstract: Background The Coronavirus disease 2019 (COVID‐19) pandemic is having a major global impact, and the resultant response in the development of new diagnostics is unprecedented. The detection of antibodies against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has a role in managing the pandemic. We evaluated the feasibility of using SARS‐CoV‐2 peptide Kode Technology‐modified red cells (C19‐kodecytes) to develop an assay compatible with existing routine serologic platforms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…Red cells were coated with short peptides derived from the SARS-CoV-2 spike protein. 2,6 These red cells laden with artificial SARS-CoV-2 spike antigens (C19-kodecytes) behave like normal red cells bearing blood group antigens in routine antibody screening assays. We first investigated the performance of the C19-kodecyte assay against convalescent plasma donor samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Red cells were coated with short peptides derived from the SARS-CoV-2 spike protein. 2,6 These red cells laden with artificial SARS-CoV-2 spike antigens (C19-kodecytes) behave like normal red cells bearing blood group antigens in routine antibody screening assays. We first investigated the performance of the C19-kodecyte assay against convalescent plasma donor samples.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] However, this rate was similar to the 91% specificity rate reported previously for the Grifols platform. 2,6 The samples from negative controls had not been tested with the virus neutralization assay, so a comparison was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In continuation of the previous work, the possibility of using erythrocytes (C-19 kodecytes) modified using Kode-technology function-spacer-lipid constructs and carrying short SARS-CoV-2 peptides was assessed to develop an assay compatible with the existing routine serological platforms. It has been shown that C19-kodecytes are viable for use as erythrocytes of a serological reagent to detect SARS-CoV-2 antibodies using standard equipment for screening antibodies in the blood [95].…”
Section: Screening Of Sars-cov-2 Antibodiesmentioning
confidence: 99%